„Roczniki Biblioteczne”, R. LX, 2016, Wrocław: Wydawnictwo Uniwersytetu Wrocławskiego 2016, s. 410 - Wojciechowski, Jacek (Biblioteka, 2017)
„Roczniki Biblioteczne”, R. LX, 2016, Wrocław: Wydawnictwo Uniwersytetu Wrocławskiego 2016, s. 410